Barriers and facilitators to the implementation and adoption of improvement coaching: A qualitative evidence synthesis. Issue 1 (10th April 2022) - Rushton, Sharron; Lewinski, Allison A.; Hwang, Soohyun; Zullig, Leah L.; Ball Ricks, Katharine A.; Ramos, Katherine; Gordon, Adelaide; Ear, Belinda; Ballengee, Lindsay A.; Brahmajothi, Mulugu V.; Moore, Thomasena; Blalock, Dan V.; et al.
Abstract: Background: Healthcare organisations and teams perform improvement activities to facilitate high‐quality healthcare. The use of an improvement coach who provides support and guidance to the healthcare team may facilitate improvement activities; however, no systematic review exists on the facilitators and barriers to implementing an improvement coach. Aims: We conducted a qualitative evidence synthesis to examine the facilitators and barriers to the implementation of improvement coaching. Methods: We searched MEDLINE ®, Embase and CINAHL. The final search was in March 2021. The screening eligibility criteria included the following: interdisciplinary team receiving the coaching, improvement coaching, designs with a qualitative component and primary purpose of evaluating practice facilitation in OECD countries. An ecologically‐informed consolidated framework for implementation research (CFIR) served as the framework for coding. Patterns of barriers and facilitators across domains were identified through matrix analysis. Risk of bias was assessed using Critical Appraisal Skills Program. PRISMA reporting guidelines served as a guide for reporting this review. Results: Nineteen studies with a qualitative component met the inclusion criteria. Four themes of barriers and facilitators crossed multiple CFIR domains: adaptability (e.g. making adjustments to the project; process, or approach); knowledge and skills (e.g. understanding of content and process for the project); engagement (e.g. willingness to be involved in the process) and resources (e.g. assets required to complete the improvement process). Conclusion: Improvement coaching is a complex intervention that influences the context, healthcare team being coached and improvement activities. Improvement coaches should understand how to minimise barriers and promote facilitators that are unique to each improvement project across the domains. Limitations of the study are related to the nature of the intervention including potential publication bias given quality improvement focus; the variety of terms similar to improvement coaching or selection of framework.